Hazy Bloom and the mystery next door - Hamburg, Jennifer (Hamburg, Jennifer. Hazy Bloom., 2019)
"When Hazy Bloom gets a tomorrow vision of a ghost flying around the empty house next door, her boring summer vacation suddenly takes a mysterious, thrilling, and hilariously Hazy-like turn"--